2014
DOI: 10.1074/jbc.m113.517177
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of the Retinal Glutamate Transporters GLT-1c and EAAT5

Abstract: Background: GLT-1c and EAAT5 are two excitatory amino acid transporters co-expressed in retinal neurons. Results: GLT-1c and EAAT5 differ in glutamate and Na ϩ affinity, individual transport rates as well as in unitary anion current

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 44 publications
3
54
0
2
Order By: Relevance
“…10 increases in D-aspartate uptake for both hEAAT5 and hEAAT5v are consistent with data from recent studies showing that EAAT5 is a slow, low capacity glutamate transporter (Gameiro et al, 2011;Schneider et al 2014). The apparant K m value for D-aspartate was ~54 µM (Fig 3B), which is in agreement with the previously reported value for hEAAT5 (Arriza et al, 1997).…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 92%
“…10 increases in D-aspartate uptake for both hEAAT5 and hEAAT5v are consistent with data from recent studies showing that EAAT5 is a slow, low capacity glutamate transporter (Gameiro et al, 2011;Schneider et al 2014). The apparant K m value for D-aspartate was ~54 µM (Fig 3B), which is in agreement with the previously reported value for hEAAT5 (Arriza et al, 1997).…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 92%
“…In transporters with a normal substrate-gated anion conductance, application of saturating concentrations of glutamate would be expected to result in a 2-3-fold increase in the current amplitude. This has been consistently observed for EAAT2 (6), EAAT3 (37), EAAT4 (6,9,30), and EAAT5 (38). As predicted, oocytes expressing EAAT1 WT displayed current amplitudes in the presence of 1 mM glutamate that were 3-fold larger than in its absence (Fig.…”
Section: -I)supporting
confidence: 84%
“…4B and Table 1), together with the inability of substrate to further activate the anion conductance, strongly suggest that the anion channel exists in a constitutively open state. The activation of EAATassociated anion channels has also been observed to be voltagedependent (6,(37)(38)(39)(40). In oocytes expressing EAAT1 WT, we observed a voltage-dependent relative open probability with a V 50 of Ϫ25.6 Ϯ 1.2 mV (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…EAAT4 has the highest affinity with reported Km values in the range 0. 6-3.3 µM (Fairman et al, 1995;Lin et al, 1998;#19512};Mim et al, 2005), while EAAT5 has the lowest affinity with Km values in the range 61-63 µM (Gameiro et al, 2011;Schneider et al, 2014).…”
Section: Identification Of Plasma Membrane Glutamate Transportersmentioning
confidence: 99%
“…EAAT5 (Arriza et al, 1997) is present in the retina at significant levels (Eliasof et al, 1998;Veruki et al, 2006;Schneider et al, 2014), and it may be subject to variable splicing (Lee et al, 2012), but has not been reported in other parts of the central nervous system. It is present in vestibular hair cells (Dalet et al, 2012), in the heart (Arriza et al, 1997;Martinov et al, 2014), in skeletal muscle (Arriza et al, 1997) and possibly at low levels in several other peripheral organs (Lee et al, 2013).…”
Section: Eaat4mentioning
confidence: 99%